2023
DOI: 10.1021/acs.orglett.3c02364
|View full text |Cite
|
Sign up to set email alerts
|

Double Bond Geometric Isomers of Pentaketide Ansamycins from Streptomyces sp. S008

Shengliang Zhao,
Chunhua Lu,
Haoxin Wang
et al.

Abstract: Six new pentaketide ansamycins, namely, shengliangmycins A−F (1−6, respectively), were obtained from the fermentation products of Streptomyces sp. S008OEslmR2 that was derived by constitutive expression of LAL regulator gene slmR2. The structures of 1−6 were determined through comprehensive spectroscopic analysis and single-crystal X-ray diffraction. Compound 1 has a cis-C6�C7 bond, which is different from that of compounds 2−5. Compounds 3−6 feature a morpholinone structural moiety, whereas 5 is characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…A review of the literature revealed that 7 was identical with shengliangmycin C, reported in 2023 from a genetically modified Chinese soil-derived Streptomyces. Importantly, this earlier study had confirmed the structure and absolute configuration of 7 by an X-ray analysis, as the 4-epimer of 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature revealed that 7 was identical with shengliangmycin C, reported in 2023 from a genetically modified Chinese soil-derived Streptomyces. Importantly, this earlier study had confirmed the structure and absolute configuration of 7 by an X-ray analysis, as the 4-epimer of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Shengliangmycin C (7). Colorless powder; [α] D 24 – 242 ( c 0.01, MeOH); 1D and 2D NMR (DMSO- d 6 ) see Table S9 and Figures S53–S59, identical with literature; HRESIMS m / z 368.1465 [M + Na] + (calcd. for C 19 H 23 NNaO 5 , 368.1468).…”
Section: Methodsmentioning
confidence: 99%
“…Activation of a cryptic gene cluster from Streptomyces species S008O has led to the discovery of six new pentaketide ansamycins. 27 Constitutive expression of the LAL regulator gene slmR2 led to polyketides such as shengliangmycin E 36 , which has an unusual pyrazoline ring.…”
mentioning
confidence: 99%
“…According to the polyketide chain length, known ansamycins are classified into several subgroups, and pentaketide ansamycins are the smallest. Eight different types of pentaketide ansamycins have been reported, including Q-1047, tetrapetalones, , cebulactams, juanlimycins, microansamycins, aminoansamycins, catellatolactams, and shengliangmycins . Tetrapetalones represent a unique group of pentaketide ansamycins, which were first isolated from the culture broth of Streptomyces sp.…”
mentioning
confidence: 99%